Electro-Chemical Properties of Selected Oxisols and Ultisols of Kerala with Special Reference to Charge Characteristics and Surface Mineralogy - Rajendran P (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1992)
A study has been conducted in seven selected profiles of Oxisols and Ultisols representing the important pedological units with a wide geographical distribution in the state to have a deeper insight in to the electro-chemical behaviour of these soils. A multipronged approach to the studies made are highlighted to enable a clear understanding of the achievements as against the major objectives and approaches made. A laboratory study with thirty six samples from seven profiles representing six Ultisols and one Oxisol has been carried out. Path coefficient analysis of important thirteen charge contributing factors against two parameters for measurement of charge and the inter-relationship of 15 soil characters show that organic matter5, clay %, R2 O3%, Alo% and Feo% are the major factors that control the surface charge behaviour of the soils. The factors studied explained only 55% and 48% of the variability of cation exchange and anion exchange respectively. Study of the distribution of the electric charges in the surface and sub- surface horizons of the soils was made by the means of potentiometric titrations and by measurement of adsorption of ions in the presence of varying concentration of electrolytes. The titration curves at different ionic strengths crossed at the common point intersection the zero-point of charge (zpc). Thus the electro-chemical behaviour of these soils was found to be similar to that exhibited by many metallic oxides in which the surface potential of reversible double layer is determined solely by the activity of potential determining ions, H+ and OH- in the bulk of the solution. The zpc for the surface horizons was found to be lower than the sub-surface and sub- surface horizons in all the soils studied. Soil to soil variation in zcp between surface and sub-surface horizons were more or less the same for all samples. Thus zcp can not be recommended as a taxonomic tool in soil classification to distinguish Oxisols from Ultisols. From known values of surface area and zpc of these soils, the values for net electric charge was calculated by the application of the Gouy- Chapman model of double layer and was found to obey the theory only at a critical electrolyte concentration. As the soils were found to be similar to that of constant potential systems, the charge distribution varied substan\tially with PH and electrolyte concentration. Direct measurement of adsorption of ions from solutions of KC1 NaCl and CaCl2 showed that the nature and valence of index cations also influenced the magnitude of the negative charges on the soils particles. On the basis of the influence of PHJ, electrolyte concentration and the valence of the counter-ions on the electric charges of the soils most of the conventional methods of ion-exchanged determinations using buffered electrolytes at high concentrations appears to be inappropriate for tropical soils. In a study for the evaluation of ion-exchange measurements it was found that the compulsive exchange methods is most suitable for the combined estimation of CEC and AEC. The traditional ammonium acetate method was found to give over estimations of CEC and thus very high values. Calcium chloride, 0.002 M was found to be equally effective but owing to the simplicity of the procedure, the former appeared better. The compulsive exchange method is free from the inherent defects of neutral normal ammonium acetate and hence would seem well suited for the Oxisols and Ultisols of Kerala. Although sesquioxidic components in combination with organic matter apparently dominate the charge properties of these soils, there was evidence from the titration curves to shows the presence of small amounts of clay minerals with permanent negative charge. This was confirmed by different methods and was found in good agreement with the estimated theoretical results. However under field conditions the expression of this constituent was minimum and the variable charge components such as Fe, al oxides certainly control the electro-chemical characteristics. In a separate experiment to find out the contribution of organic matter and sesquioxides towards exchanges properties of soils, it was observed that bout 64% of the negative sites and 8% of the positive was contributed from organic matter. Sesquioxides explained only 11% of the variablility in CECX and 22% of the variability in AEC. The combined effect of organic matter and R2O3 removal was highly significant with respect to CEC and AEC in all the soils studied. Mineralogical investigation revealed the presence of kaolinite as the dominant clay mineral. Appreciable amounts of smectities, quartz and gibbsite was also identified. The presence of smectities was not reflected in the CEC of any of the samples. Scanning electron micrographs did not give much information other than the presence of a thick coating of iron and amorphous materials over clay aggregates. The specific surface measured by ethylence glycol retention method invariably showed higher values than the determined values obtained for negative adsorption data. The specific surface determined closely followed the organic matter content of the samples inspite of the vertical increase in clay content with in profiles.